The effect of polymer solubilizing side-chains on solar cell stability1. Issue 17 (7th May 2015) - Morse, Graham E.; Tournebize, Aurélien; Rivaton, Agnès; Chassé, Thomas; Taviot-Gueho, Christine; Blouin, Nicolas; Lozman, Owen R.; Tierney, Steven
<x xml:space="preserve">Abstract</x> The impact of polymer side-chains on encapsulated OPV device stability is studied systematically in a series of low bandgap polymers.